PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTU SOFTWARE GEOGEBRA - Slamet; Benny Hendriana; Gita Halimah (Prosiding Seminar Nasional Berseri, 2020)
The aim of this class action is to increases mathematic learning outcomes’ students’ at XI- Science 1 in 13 Senior High School, Bekasi. The type of the research is using by Classroom Action Research (CAR) uses two cycles each cycles consist by four steps are planning, implementation, observation, and reflection. The data collecting techniques by learning outcome test and the activites study students in from of the observation. Pre cycle was taken from the score of daily exam about Mathematical Induction, with the average value was obtained 61,1. The result of this research showing there is any enhancement result study mathematic students seen from the average score 68,22 at the first cycle and 90,56 at the second cycle, and then enhancement student reached the average 25% pre cycle, 38,89 on first cycle, and 91,67% on second cycle. The enhancement percentage teacher activity at first cycle is 80% and the enhancement percentage teacher activity at second cycle is 84%. The enhancement student activity at first cycle is 83,33% and the enhancement student activity at second cycle is 87,5%. With all of this it can be conclude that model cooperative learning type jigsaw assisted software geogebra can increases student learning outcomes’ at XI-Science 1in 13 Senior High School, Bekasi.